“SCIENTIFIC AND THEORETICAL FOUNDATIONS FOR THE STUDY OF ANTHROPONYMS AND TOPONYMS IN THE TEXT “BABURNAME” (World Bulletin of Social Sciences, 2023)
The study of all toponymic scale units, such as oikonyms, hydronyms, oronyms and necronyms, which have their place in linguistics, is put on the agenda based on new linguistic paradigms. It is important to study toponyms in all respects, dwell on the history of their origin, analyze them from the philosophical and social side, interpret their expression by artistic and illustrative means. We will analyze types of toponyms in the text of “Baburnama”.